Mandated College Students’ Response to Sequentially-Administered Alcohol Interventions in a Randomized Clinical Trial Using Stepped Care - Borsari, Brian (J Consult Clin Psychol, 2015)
OBJECTIVE: Students referred to school administration for alcohol policies violations currently receive a wide variety of interventions. This study examined predictors of response to two interventions delivered to mandated college students (N = 598) using a stepped care approach incorporating a peer-delivered 15-minute BA session (BA; Step 1) and a 60–90 minute brief motivational intervention delivered by trained interventionists (BMI; Step 2). METHOD: Analyses were completed in two stages. First, three types of variables (screening variables, alcohol-related cognitions, mandated student profile) were examined in a logistic regression model as putative predictors of lower-risk drinking (defined as 3 or fewer heavy episodic drinking [HED] episodes and/or 4 or fewer alcohol-related consequences in the past month) six weeks following the BA session. Second, we used generalized estimating equations to examine putative moderators of BMI effects on HED and peak blood alcohol content (pBAC) compared to assessment-only control (AO) over the 3, 6, and 9 month follow-ups. RESULTS: Participants reporting lower scores on the Alcohol Use Disorders Identification Test (AUDIT), more benefits to changing alcohol use, and those who fit the ‘Bad Incident’ profile at baseline were more likely to report lower risk drinking 6 weeks after the BA session. Moderation analyses revealed that ‘Bad Incident’ students who received the BMI reported more HED at 9-month follow up than those who received AO. CONCLUSION: Current alcohol use as well as personal reaction to the referral event may have clinical utility in identifying which mandated students benefit from treatments of varying content and intensity.